Low-temperature plasma improves the healing process of Achilles tendinopathy in a rat model - Wang, Suying; Li, Juan; Pan, Qingyan; Li, Jiahe; Zhao, Long; Zhou, Yuhan; Wang, Gang; Zhou, Ming; Liu, Yangxiaoxue; Wang, Aiguo; Huang, Liping; Chen, Xiaoran (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundTendinopathy is a prevalent condition in orthopedics that significantly impairs tendon function. Recently, Low-temperature plasma (LTP) has emerged as an innovative treatment approach, showing promise in reducing inflammation and enhancing collagen synthesis during wound healing. This study aimed to evaluate the therapeutic benefits of LTP on Achilles tendinopathy.MethodsThe effectiveness of LTP in treating Achilles tendinopathy was confirmed using an excessive exercise rat model, through assessments of biomechanical properties and pathological alterations. Type I and III collagen expression and mRNA levels of inflammatory factors were further detected. Blood flow and NO concentration finally examined.ResultLTP therapy markedly enhanced the biomechanical characteristics of the Achilles tendon, including maximum tension, stress, stiffness, and Young’s modulus. Correspondingly, histomorphometric analysis showed a significant improvement in the pathological alterations of the Achilles tendon and a decrease in the pathology score.Additionally, increased expression of collagen type I and decreased the ratio of collagen type III to collagen type I were observed after LTP treatment. Further, LTP treatment significantly inhibited the expression of cyclooxygenase-2 (COX-2),interleukin 1-β (IL-1β), tumor necrosis factor alpha (TNF-α), matrix metalloproteinase 1 (MMP-1), and matrix metalloproteinase 2 (MMP-2). Specifically, enhanced blood flow in the Achilles tendon was noted following LTP treatment. Intriguingly, LTP therapy also significantly increased nitric oxide (NO) levels in the skin, blood, and Achilles tendon.ConclusionLTP exhibited a significant therapeutic impact on tendinopathy by inhibiting inflammation, promoting type I collagen synthesis, and enhancing blood flow, which may related to the active NO in LTP jet.